“An Invisible Tide” - Jo [M.] Thomas (The Future Fire: Social Political & Speculative Cyber-Fiction, 2015)
The story is set in a polluted future in Wales, where the algal blooms have destroyed fishing and an invisible tide of toxic gas forces everyone to wear protective gear.
Keywords: English author; Female author